The role of decavanadate in anti-tumor activity - Aureliano, M. (2017)
Decavanadate compounds were described to be involved in a variety of biological activities and responses such as anti-virus, anti-bacterial and anticancer. While the mechanisms of action of the antiviral and anti-bacterial activities are better understood, the same does not go for the anti-tumour activity. Nevertheless, the inhibition of tumour proliferation seems to impact certain enzymes such as alkaline phosphatase, ecto-nucleotidases or P-type ATPases. In the present report, several studies are described, in a way to explain the increasing interest of these polyoxometalate in cancer therapy. The detailed knowledge of the molecular basis of decavanadate–proteins and cellular interactions allows to better understand the processes associated with the anticancer applications, not only for decavanadate but as well for other polyoxometalates (POMs).